Faktor Risiko Kejadian Green Tobacco Sickness (GTS) pada Buruh Tani Tembakau: Literature Review: Risk Factors for Green Tobacco Sickness (GTS) in Tobacco Farm Workers: Literature Review - Audini Fathia Rizki; Nur Endah Wahyuningsih; Budiyono Budiyono (Jurnal Sains dan Kesehatan, 2021)
Abstract Background: Background: Green Tobacco Sickness (GTS) is a form of nicotine poisoning caused by direct contact between the skin of tobacco farm workers and wet tobacco plants during the planting and harvesting process. This study aims to analyze the risk factors for the incidence of GTS in tobacco farmers. Method: The method used was a literature review. Articles were obtained from the online database Scopus, PubMed, ProQuest, Google Scholar, and Garuda Portal published during 2010-2020. The selected article used an observational study design and discussed the risk factors for the incidence of GTS in tobacco farmers. The assessment of the quality of the articles used guidelines from the Joanna Briggs Institute. Based on the article search, twelve articles were consisting of three articles from national journals and nine articles from international journals. Article analysis was carried out by comparing the percentage of significant variables in the entire article. This study resulted in the most dominant risk factor for GTS is the use of personal protective equipment with a percentage of 50% of the total articles.